Influence of Aloe vera on water absorption and enzymatic in vitro degradation of alginate hydrogel films - Pereira, Rúben F. (2013)
This study investigates the influence of Aloe vera on water absorption and the in vitro degradation rate of Aloe vera-Ca-alginate hydrogel films, for wound healing and drug delivery applications. The influence of A. vera content (5%, 15% and 25%, v/v) on water absorption was evaluated by the incubation of the films into a 0.1 M HCl solution (pH 1.0), acetate buffer (pH 5.5) and simulated body fluid solution (pH 7.4) during 24 h. Results show that the water absorption is significantly higher for films containing high A. vera contents (15% and 25%), while no significant differences are observed between the alginate neat film and the film with 5% of A. vera. The in vitro enzymatic degradation tests indicate that an increase in the A. vera content significantly enhances the degradation rate of the films. Control films, incubated in a simulated body fluid solution without enzymes, are resistant to the hydrolytic degradation, exhibiting reduced weight loss and maintaining its structural integrity. Results also show that the water absorption and the in vitro degradation rate of the films can be tailored by changing the A. vera content.